Judge's Consideration of Plagiarism Criteria: Analysis of Decision No. 31/PDT.SUS-COPYRIGHT/2020/PN.JKT.PST (International Forum of Researchers and Lecturers, 2025)
This research aims to determine the criteria for fine arts plagiarism according to Law Number 28 of 2014 concerning Copyright. Apart from that, it also aims to find out the basis of the judge's considerations in Decision Number 31/Pdt.Sus-Hak Copyright /2020/ Pn.Jkt.Pst. In this research, the method used is normative legal research which is prescriptive in nature. Normative nature prescriptive that is method with research ingredients​​ literature indicated in the written regulations.​ Method approach used​ in writing law This is method approach cases and approaches legislation. Result of study This According to Law Number 28 of 2014 concerning Copyright, the criteria for plagiarism of works of art are if they meet the elements 1) there is a substantial similarity in whole or in part, 2) there is confession owned by personal to work imitation and 3) cause loss for creator on imitation work. In The judge's consideration in deciding the alleged case of fine art plagiarism took into account 1) Proving the similarity between Love Light and Urban Light; 2) There are losses arising for the Plaintiff. In this case, the judge's considerations were in accordance with the regulations of Law Number 28 of 2014 concerning Copyright and the Plaintiff was also able to prove everything so that the Defendant was found guilty.